An investigation of association between chronic musculoskeletal pain and cardiovascular disease in the Health Survey for England (2008). (24th October 2013) - Ryan, C.G.; McDonough, S.; Kirwan, J.P.; Leveille, S.; Martin, D.J.
Abstract Background Chronic musculoskeletal pain (CMP) may be associated with cardiovascular disease (CVD). This study aimed to investigate the association between CMP and CVD, and the contribution of physical activity and sedentary behaviour to any association. Methods We performed a secondary analysis of 3332 middle‐aged (45–64 years) and 2022 older (65+ years) adults included in the Health Survey for England (2008). The survey contained self‐reported physical activity/sedentary behaviour data. Objectively measured physical activity/sedentary behaviour using accelerometry (Actigraph™) was also available for a subset of the middle‐aged (n = 715) and older (n = 492) participants. Logistic regression examined the association between CMP and CVD adjusted for self‐reported and objectively measured physical activity, sedentary behaviour and a range of other CVD risk factors. Results There was a higher prevalence of CVD in those with CMP for both the middle‐aged (22.5% vs. 13.5%) and the older (46.8% vs. 28.2%) adults (p < 0.001). After adjusting for CVD risk factors, older adults with CMP were significantly more likely to have CVD {odds ratio [95% confidence interval (CI)] 1.828 (1.452, 2.300); p < 0.001}. A similar non‐significant trend was shown for the middle‐aged adults [odds ratio (95% CI) 1.271 (0.975, 1.656); p = 0.076]. Neither self‐reported nor objectively measured physical activity (or sedentary behaviour) had any meaningful effect on the association between CMP and CVD. Conclusions CMP is associated with an increased risk of CVD and the association is stronger in older adults. Neither physical activity nor sedentary behaviour contributed to this relationship. Longitudinal studies are warranted to better understand the relationship between CVD and CMP.